Clinical features and prognosis analysis of 358 cases of permanent immature teeth crown fracture - ZHANG Lingyu, ZHANG Qiong, ZOU Jing (口腔疾病防治, 2024)
Objective To investigate the clinical characteristics and prognosis of crown fractures in immature permanent incisors due to trauma, and identify factors affecting their prognosisto provide a reference for clinical treatment. Methods This study was approved by the Medical Ethics Committee of West China Stomatology Hospital, Sichuan University. The study subjects were patients admitted to the pediatric stomatology department from December 2011 to December 2021, and a retrospective analysis was conducted on young permanent teeth with anterior crown fracture caused by injury and followed up for at least 1 year, which were diagnosed as enamel fractures, enamel-dentin fractures, and complicated crown fracture and treated by observation, pulpotomy etc. in the first appointment. The age, sex and time elapsed from trauma to baseline visit of the patients and the location, mobility, stage of root development, diagnosis and treatments were collected. The occurrence of pulp infection, pulp necrosis, and other events in the affected tooth is defined as clinical failure. Record whether clinical failure occurred and the timing of their occurrence of the traumatized tooth. Analyze factors related to the prognosis of various types of crown fractures in young permanent incisors and performsurvival analysis on the affected teeth. Results Among 358 cases of young permanent incisors, 50 cases were diagnosed with enamel fracture, 176 cases with enamel-dentin fracture, and 132 cases with complicated crown fracture. The clinical success rate of crown fractures was 73.7% (264/358) in young permanent incisors. The incidence rates of clinical failure cases, including pulp infection and necrosis, were 4% (2/50) for enamel fractures, 33.3% (58/176) for enamel-dentin fractures, and 25.8% (34/132) for complicated crown fractures respectively. The clinical failure rate of enamel-dentin fracture treated with indirect pulp capping and restoration was higher than restoration only and pulpotomy (χ2 = 10.077, P = 0.004). The clinical failure rate of complicated crown fractures treated with direct pulp capping was higher than pulpotomy (χ2 = 5.501, P = 0.038). The clinical failure rates between observation, smoothing edges and restoration of enamel fractures exhibit no significant differences (χ2 = 0.588, P = 0.999). Risk factors for clinical failure in this study population included patient age over 9 years old (HR = 2.11, 95%CI: 1.1-3.9, P = 0.017)、time elapsed from trauma to baseline visit greater than 3 days (HR = 2.3, 95%CI: 1-4.8, P = 0.028), traumatized teeth with mobility (HR = 1.95, 95%CI: 1.2-3, P = 0.004), enamel-dentin fractures treated with restoration (HR = 6.89, 95%CI: 1.6-29.6, P = 0.010), enamel-dentin fractures treated with indirect pulp capping and restoration (HR = 13.8, 95%CI: 3.2-58.3, P<0.001) and complicated crown fractures treated with direct pulp capping (HR = 46.07, 95%CI: 8-263.8, P<0.001). Conclusion Enamel fractures treated by observation, smoothing edges and restoration, and complicated crown fractures treated with pulpotomy generally had a good prognosis in young permanent incisors. Close follow-up was recommended for crown fractures in young permanent incisors with identified risk factors for poor prognosis.